ANALISIS MEDIA SOSIAL INSTAGRAM SEBAGAI MEDIA PROMOSI KEDAI WAFFLE BOX - Rahayu, Eka Yunita (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2020)
The purpose of this study is to find out how the editor-in-chief in directing journalists to find news so that they are able to produce quality news and find out how journalists understand the instructions given by the chief editor. The research method used is descriptive qualitative research with the research location located at Radar TV Palu, Jalan Yos Sudarso No. 9 Hammers. the informants in this study amounted to 4 (four) informants who were selected through purposive sampling. Data collection techniques were carried out by observation (participants) and interviews. The data analysis technique used qualitative data analysis. The results of this study indicate that the editor-in-chief's communication style to journalists on Radar TV Palu has indeed been carried out by the editor-in-chief, this is because all instructions or directives from the editor-in-chief to journalists have been carried out, although not entirely. There are four communication style orientations used by the editor-in-chief of Radar TV Palu, namely action-oriented communication style, process-oriented communication style, people-oriented communication style and idea-oriented communication style. However, of the four communication styles, the most prominent leadership style used by the editor-in-chief of Radar TV Palu is a people-oriented communication style because it is humane, can share feelings and is also based on his experience in the field of journalism or being a journalist so that he can understand every process. by journalists. Meanwhile, in carrying out any instructions or directions given by the editor-in-chief of Radar TV Palu, it has been carried out by journalists, to carry out this is not difficult because the relationship between the editor-in-chief and all journalists is very well established and that also makes it easier for the editor-in-chief in giving directions even though the direction it's not maximally done by journalists.